Fresh funds for moms: feasibility of a 12-week online food as medicine grocery prescription program for women with food insecurity and gestational diabetes - Gillespie, Rachel; Maksi, Sara J.; Bush, Joshua; Cockerham, Cynthia; Luecking, Courtney T.; Deierlein, Andrea L.; Wasser, Heather; Gustafson, Alison (Frontiers in Health Services, 2025)
IntroductionPregnant women with food insecurity experience high rates of gestational diabetes mellitus (GDM). Food as medicine and grocery prescription (GPx) programs have been successful in increasing food access and managing chronic disease; however, they are often not implemented during pregnancy.MethodsThis was a pilot study of Fresh Funds for Moms, an online grocery prescription (GPx) program. Pregnant women between 20 and 28 weeks' gestation were purposefully recruited from one large hospital system in an urban community in Kentucky. Eligibility included: positive screening for food insecurity; diagnosis of either GDM, type 2 diabetes, or hypertension; and live in a zip code with online grocery service delivery access. Women received $200 per month for 12 weeks (total of $600) for healthy food purchases on an online grocery platform.ResultsA total of 1,163 women were initially screened; 20 women were referred to participate in the program and 14 completed the program. On average, women redeemed 96.1% of their grocery benefit throughout the pilot GPx program. Fruit and vegetable purchases increased 4% from months one to three (27%–31%), while the percentage of funds spent on meat food items decreased from 31% to 22% by the third month, and percentage spent on pantry items remained consistent month-to-month (4%). Qualitative findings highlight overall satisfaction, however, participants reported some transactional confusion when redeeming their funds on the online grocery platform and a desire for more variety when selecting food items for delivery. Blood glucose and blood pressure improved slightly, however no clinically meaningful changes in HgbA1c were observed.DiscussionThis pilot study demonstrated the feasibility of implementing a GPx program in collaboration with clinical, research, and industry partners as a food as medicine intervention. Online GPx programs have the potential for improving healthy shopping habits among pregnant women. However, to improve screening, referral, and enrollment, a larger system approach is needed to meet patients' needs, warranting further investigation in larger, adequately powered studies.